MARITIME CONNECTIONS AND CROSS-CULTURAL CONTACTS BETWEEN THE PEOPLES OF THE NUSANTARA AND THE EUROPEANS IN THE EARLY EIGHTEEN CENTURY - Hendrik E. Niemeijer (Department of History, Faculty of Humanities, Diponegoro University, 2016)
In this paper, I would like to discuss two extraordinary tales of two rather ordinary individuals in the service of the Dutch East India Company (henceforth: VOC), the first a Dutchman, Jacob Janssen de Roy, and the second a German, Georg Naporra (1731-1793). It is important to understand that all cross-cultural contacts between the peoples in the archipelago and westerners depended on seaborne trade and the vessels which plied the maritime routes. This was the only means of transportation and communication. As a consequence, cross-cultural contacts took place mainly in the port cities and coastal trading outposts. This can be clearly seen in the cases of our two ordinary Europeans: Jacob de Roy and Georg Naporra.